A Cancer-Specific Qualitative Method for Estimating the Proportion of Tumor-Infiltrating Immune Cells - Xiao, Huiting; Zhang, Jiashuai; Wang, Kai; Song, Kai; Zheng, Hailong; Yang, Jing; Li, Keru; Yuan, Rongqiang; Zhao, Wenyuan; Hui, Yang (Frontiers in Immunology, 2021)
Tumor-infiltrating immune cells are important components in the tumor microenvironment (TME) and different types of them have different effects on tumor development and progression, which depend on cancer type. Several methods have been developed for estimating the proportion of immune cells using bulk transcriptome data. However, there are lacks of methods designed for predicting the immune contexture in specific types of cancer. Besides, the existing methods were based on the absolute gene expression, which were susceptible to experimental batch effects resulting in incomparability across different datasets. In this study, take colorectal cancer (CRC) and melanoma for example, we introduced the Tumor-infiltrating Immune Cell Proportion Estimator (TICPE), a cancer-specific qualitative method for estimating the proportion of tumor-infiltrating immune cells. The TICPE based on the relative expression orderings (REOs) of gene pairs within a sample was notably insensitive to batch effects. Performance evaluation on public expression data with mRNA mixtures, single-cell RNA-Seq (scRNA-Seq) data, and immunohistochemistry data indicated that TICPE could estimate the proportion of immune cells with superior accuracy to other methods. Furthermore, we showed that TICPE could effectively detect prognostic signals in tumor patients and immune cells fraction changes during immunotherapy, as well as establish an association between anti-PD-1 treatment response and elevated CD8+ T cell and NK cell levels in melanoma patients. In conclusion, our work presented a unique novel method TICPE to estimate the proportion of immune cells in specific cancer types and explore the effect of the infiltration of immune cells on the immunotherapy and prognosis of cancer. The source code for TICPE is available at https://github.com/huitingxiao/TICPE.